Reference ranges for fetal brain structures using magnetic resonance imaging: systematic review. (10th February 2022) - Di Mascio, D.; Khalil, A.; Rizzo, G.; Kasprian, G.; Caulo, M.; Manganaro, L.; Odibo, A. O.; Flacco, M. E.; Giancotti, A.; Buca, D.; Liberati, M.; Timor‐Tritsch, I. E.; et al.
ABSTRACT: Objective: To evaluate the methodology of studies reporting reference ranges for fetal brain structures on magnetic resonance imaging (MRI). Methods: MEDLINE, EMBASE, CINAHL and the Web of Science databases were searched electronically up to 31 December 2020 to identify studies investigating biometry and growth of the fetal brain and reporting reference ranges for brain structures using MRI. The primary aim was to evaluate the methodology of these studies. A list of 26 quality criteria divided into three domains, including 'study design', 'statistical and reporting methods' and 'specific aspects relevant to MRI', was developed and applied to evaluate the methodological appropriateness of each of the included studies. The overall quality score of a study, ranging between 0 and 26, was defined as the sum of scores awarded for each quality criterion and expressed as a percentage (the lower the percentage, the higher the risk of bias). Results: Fifteen studies were included in this systematic review. The overall mean quality score of the studies evaluated was 48.7%. When focusing on each domain, the mean quality score was 42.0% for 'study design', 59.4% for 'statistical and reporting methods' and 33.3% for 'specific aspects relevant to MRI'. For the 'study design' domain, sample size calculation and consecutive enrolment of women were the items found to be at the highest risk of bias. For the 'statistical and reporting methods' domain, the presence of regression equations for mean and SD for each measurement, the number of measurements taken for each variable and the presence of postnatal assessment information were the items found to be at the highest risk of bias. For the 'specific aspects relevant to MRI' domain, whole fetal brain assessment was not performed in any of the included studies and was therefore considered to be the item at the highest risk of bias. Conclusions: Most of the previously published studies reporting fetal brain reference ranges on MRI are highly heterogeneous and have low‐to‐moderate quality in terms of methodology, which is similar to the findings reported for ultrasound studies. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.